Molecular Regulation of Noradrenaline in Bovine Corpus Luteum - ANOM BOWOLAKSONO (HAYATI Journal of Biosciences, 2012)
Noradrenergic stimulation increases progesterone, oxytocin and prostaglandins in the bovine luteal tissue. Better understanding of noradrenaline (NA) role in bovine the corpus luteum (CL) can advance our current knowledge on the regulatory mechanism of CL function. The present study was conducted to explore the source of noradrenaline and further to investigate whether nerve growth factor (NGF), insulin like growth factor 1 (IGF1) and transforming growth factor b1 (TGFb1) influence the expression of dopamine-b-hydroxylase (DBH), biosynthetic enzyme of NA in cultured bovine luteal cells. Corpora lutea were collected and classified into stages of early, developing, mid, late, and regressed. Messenger RNA (mRNA) and protein expression of DBH were studied throughout the estrous cycle. Additionally, DBH protein expression was examined in cultured mid luteal cells after tumour necrosis factor alpha/interferon gamma (TNFa/IFNg)-induced apoptosis or after treatment with NGF, IGF1, and TGFb1. DBH mRNA and protein expressions were detected throughout the cycle without significant changes in the protein level while mRNA showed a decrease at the developing stage (P < 0.05). Interestingly, NGF, IGF1, and TGFb1 increased DBH expression in cultured luteal cells (P < 0.05). The overall findings suggest non-neural source of noradrenaline in the bovine CL which appears to be regulated by NGF, IGF1, and TGFb1 indicating intraluteal molecules play an important and unrecognized role in the CL function.